Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien di Rumah Sakit Sumatera Utara: - Intan Syahdilla; Putri Sonia; Riza Faradiba; Sri Mulyani; Yowanda Pasyah; Dewi Agustina (Transformasi Manageria: Journal of Islamic Education Management, 2023)
The hospital is a health service institution for the community with its own characteristics which are influenced by developments in health science, technological advances, and the socio-economic life of the community which must continue to be able to improve services that are of a higher quality and are affordable to the community in order to realize the highest degree of health. In hospital health services patient satisfaction is one indicator of the quality of health services. Patient satisfaction is an integral and comprehensive part of health service quality assurance activities. Public perception of the quality of health services and their impact on the utilization of health services is the main indicator of the success of health services. This study aims to analyze the effect of service quality on patient satisfaction in North Sumatra hospitals. This research uses a literature review or Literature Review using the PRISMA (Preferred Reporting Items for Systematic Review) systematic review with the Google Scholar database. The results of the study include 5 measurement tools for patient satisfaction in North Sumatra hospitals, namely Physical Evidence (6 good rating journals), Responsiveness (6 good rating journals), Caring (6 good rating journals), Reliability (5 good rating journals) and Assurance (8 good rating journals). Keywords: service quality, patient satisfaction